Respostas

A melhor resposta!
2013-05-20T17:05:39-03:00

a) x +1x + 1x =4 -6

     3x= -2

     x= -2/3

     x= -0,666...

 

b) (-1x).(-8x)=34

     +8x=34

      x=34/8

      x=4,25

     

c) (-3x).(+5x) -2x=+7-46

     -15x -2x=-39

     -17x=-39

      x=(-39)/(-17)

      x=+2.2941...

 

Espero ter ajudado!

2 5 2
2013-05-20T17:24:15-03:00

a) 2x² - x + 6 = 4x +4

2x² - 4x = 4 - 6

2x² - 4x = -2

 

b) 2x² - 16x - 3x - 24 = 34

2x² -19x = 58

 

c) x² + 5x - 3x - 15 + 46 = 2x + 7

x² = -24